Strategi Pemerintah Menuju Pariwisata Berkelanjutan di Kawasan Telaga Sarangan - Antin Rakhmawati; Muhammad Nizar (LP2M Universitas Ibrahimy, 2024)
This research aims to analyze the government's strategy for realizing sustainable tourism in the Telaga Sarangan area. The main focus of the research is on the role of government as a facilitator, regulator and motivator in supporting Sustainable Development Goals (SDGs) in the region. The main problem identified is the unsustainable economic development of the surrounding community and the non-optimal use of the Sarangan Lake area as a tourist destination. The research method used is qualitative, which is done by collecting secondary data from various sources such as books, journals, articles, report documents, and statutory regulations. The research results show that the government has a crucial role as a facilitator in improving supporting facilities and infrastructure for tourists in the Telaga Sarangan area. As a regulator, the government also has the responsibility to design regulations and policies that support sustainable tourism management. However, the government's role as a motivator is still not optimal, requiring outreach efforts, training and allocation of stimulant funds to develop tourism management in the area. The conclusion of this research confirms that the government has a strategic role in achieving the SDGs in the Telaga Sarangan area through the development of sustainable tourism. Positive contributions to the economy, ecology, as well as social and cultural aspects are expected to be realized through the implementation of strategies that suit the needs and potential of the area.